2016
DOI: 10.1002/cbin.10647
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial permeability transition pore (MPTP) desensitization increases sea urchin spermatozoa fertilization rate

Abstract: Mitochondrial permeability transition pore (MPTP) is a protein complex whose opening promotes an abrupt increase in mitochondrial inner membrane permeability. Calcium signaling pathways are described in gametes and are involved in the fertilization process. Although mitochondria may act as Ca(2+) store and have a fast calcium-releasing mechanism through MPTP, its contribution to fertilization remains unclear. The work aimed to investigate the MPTP phenomenon in sea urchin spermatozoa and its role on the fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 99 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…In this study, based on increasing viability and motility of sperm, we inferred that melatonin inhibited apoptosis and improved quality of frozen-thawed sperm. Inhibition of the opening of MPTP during cryopreservation significantly reduced apoptotic markers (e.g., caspase activity) and mitochondrial membrane permeability in equine sperm (33); furthermore, it also increased m and improved fertilization in frozen-thawed sea urchin sperm (34). Therefore, results of the current study confirmed that melatonin effectively prevented cryopreservation-induced MPTP opening in ram sperm.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, based on increasing viability and motility of sperm, we inferred that melatonin inhibited apoptosis and improved quality of frozen-thawed sperm. Inhibition of the opening of MPTP during cryopreservation significantly reduced apoptotic markers (e.g., caspase activity) and mitochondrial membrane permeability in equine sperm (33); furthermore, it also increased m and improved fertilization in frozen-thawed sea urchin sperm (34). Therefore, results of the current study confirmed that melatonin effectively prevented cryopreservation-induced MPTP opening in ram sperm.…”
Section: Discussionmentioning
confidence: 99%
“…31 Close associations between MMP loss and mPTP formation have been reported in neurons, 32 and previous studies have equated a loss of MMP with mPTP formation in several cell types, 33 including spermatozoa. 17,23 In the present study, we set out to establish whether such a close association between mPTP formation and MMP depolarization existed in stallion spermatozoa, by simultaneously examining mitochondrial membrane status using JC-1, and mPTP formation using a loss of C-AM-V fluorescence. Our results demonstrate that in this cell type, a loss of MMP does not necessarily coincide with mPTP formation (Figure 1); indeed, one of the gating controls for the JC-1/C-AM-V assay used in the present study is CCCP, which collapsed MMP without any loss of C-AM-V fluorescence (and therefore no mPTP formation; Figure 1C), demonstrating that a loss of MMP may be due to reasons other than mPTP formation.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, several studies have recently emerged in which mPTP formation has been confirmed in the spermatozoa of several species, including the horse. 17 , 19 , 20 , 21 , 22 , 23 A limitation of many of these studies has been the use of downstream markers of mPTP formation, such as caspase activation, oxidative stress, loss of viability and/or motility, and mitochondrial membrane depolarisation, to quantify mPTP formation following various treatments. However, these events may be initiated by any number of insults and cannot definitively be attributed to mPTP formation in the absence of a C‐AM assay.…”
Section: Introductionmentioning
confidence: 99%
“…Using a specific inhibitor of the mPTP opening during cryopreservation significantly reduced the presence of apoptotic markers (e.g. caspase activity) and increased mitochondrial membrane permeability in equine sperm (Ferrusola et al, 2010), and it increased ΔΨm and improved fertilization in sea urchin sperm after thawing (Torrezan-Nitao, Boni, & Marques-Santos, 2016). In this study, based on increasing sperm plasmatic membrane integrity, ΔΨm, mitochondrial Cyt c concentration and fertilization whether in vitro or in vivo, we inferred that melatonin inhibited apoptosis and improved quality of frozen-thawed sperm.…”
Section: Discussionmentioning
confidence: 99%